Comparative analysis of p16 expression among African American and European American prostate cancer patients. Issue 11 (21st May 2019) - Wong, Myra; Bierman, Yaeli; Pettaway, Curtis; Kittles, Rick; Mims, Martha; Jones, Jeffrey; Ittmann, Michael
Abstract: Background: Expression of p16 is increased in a number of malignancies, including prostate cancer (PCa). Recent studies in a European cohort showed that expression of p16 is correlated with expression of the TMPRSS2/ERG (T/E) fusion protein. The T/E fusion is significantly less common in PCas in African American (AA) men. Thus, it would be predicted that p16 expression should be less common in PCas in AA men. We, therefore, sought to compare the expression of p16 in benign prostate and PCas from AA and European American (EA) men. Methods: Immunohistochemistry for p16 and ERG was performed on tissue microarrays constructed from radical prostatectomies performed on AA and EA veterans. Staining was scored and the scores compared with demographic, clinical and pathological parameters. Percent of West African ancestry in the AA cohort was assessed using ancestry informative markers. Results: Contrary to our predictions, p16 expression was similar in the cancers in the AA and EA cohorts. Consistent with prior reports, expression of p16 was quite low in benign prostate tissues from EA patients but surprisingly was significantly higher in benign tissues from AA patients. Expression of p16 was significantly associated with a family history of PCa in AA men. In addition, p16 was associated with ERG expression in AA PCa. Conclusions: While overall expression of p16 is similar in PCas from the two racial groups, the expression of p16 in benign tissues from a subset of AA men and the stronger correlation with ERG expression implies that there are different mechanisms for p16 overexpression in PCas from the two racial groups.